Underpricing in the euro area bond market: New evidence from post-crisis regulation and quantitative easing - Rischen, Tobias; Theissen, Erik (Journal of Financial Intermediation, 2021)
We conduct an extensive study of underpricing in the euro area bond market and find strong evidence of underpricing. In cross-sectional regressions we find patterns that are consistent with bookbuilding-based theories of underpricing and inconsistent with liquidity-based explanations. The underpricing has increased considerably during the financial crisis and has remained at an elevated level since. We also show that secondary market liquidity in the euro area bond market is significantly lower in the post-crisis period than pre-crisis. These results are consistent with recent US evidence and may represent unintended side effects of new regulation enacted in the wake of the financial crisis, such as Basel III and the Volcker Rule. Furthermore, our evidence suggests that the ECB’s corporate sector purchase programs has led to a decrease in underpricing.